Risk assessment and prevention of cardiovascular events in patients with obstructive sleep apnea syndrome: A narrative review - Bin Li; HuiQian Yang; XiaoXu Lv; Xu Guo; FengLei Xu; XiaoMing Li (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Study objectives: Obstructive sleep apnea syndrome (OSAS) is a causative agent of a wide range of chronic diseases, and its target organ damage is characterized by cardiovascular complications that are most common and severe. The primary objective of long-term intervention for OSAS is not only to correct the sleep architecture and reduce the incidence of hypoxemia, but also to alleviate the cardiovascular system's burden, decrease the risk of cardiovascular disease, and enhance patients' quality of life. Methods: A literature search of PubMed, SCOPUS, and Google Scholar was conducted from January 1, 2019, to May 30, 2024. A comprehensive narrative review of studies related to the impact of OSAS on cardiovascular events in the last five years was also conducted. This includes an overview of the incidence, physiologic mechanisms, risk indicators, and interventions for OSAS and various cardiovascular diseases. Results: Recent literature and studies have shown that there is a significant correlation between the prevalence of OSAS and the risk of cardiovascular disease, and that some unique dynamic factors such as shift work disorders play an important role in the assessment of the risk of cardiovascular events in patients with OSAS; however, new diagnostic tools and therapeutic strategies need to be further researched and developed to better meet the needs of clinical management. Conclusions: A comprehensive assessment of the cardiovascular risk associated with OSAS, utilizing the necessary screening tools and targeted interventions, including the application of drugs, surgery, CPAP, or lifestyle modifications, can effectively reduce or even prevent damage to its target organs. The main goal of long-term intervention for OSAS is not only to correct the sleep architecture and reduce the occurrence of hypoxemia, but also to reduce the burden on the cardiovascular system, reduce the risk of cardiovascular disease, and improve the quality of life of patients.